Emma's poem : the voice of the Statue of Liberty - Glaser, Linda; Nivola, Claire A. (Boston [Mass.] : Houghton Mifflin Books for Children/Houghton Mifflin Harcourt, 2010)
The story of Emma Lazarus, who, despite her life of privilege, became a tireless advocate for the immigrants who arrived in New York City in the 1880s and wrote a famous poem for the Statue of Liberty.
790
"The illustrations are painted with watercolors and gouache."--Title page verso.
004-008.
Includes bibliographical references (T.p. verso).
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection
Keywords: Lazarus, Emma, -- 1849-1887 -- Juvenile literature; Statue of Liberty (New York, N.Y.) -- Juvenile literature; Poets, American -- 19th century -- Biography -- Juvenile literature; Women social reformers -- New York (State) -- New York -- Biography -- Juvenile literature; Jews -- New York (State) -- New York -- Biography -- Juvenile literature; Lazarus, Emma, -- 1849-1887.; Statue of Liberty (New York, N.Y.); Poets, American -- 19th century -- Biography; Women social reformers -- New York (State) -- New York -- Biography; Jews -- New York (State) -- New York -- Biography; Poets, American; Reformers; Jews; 1800-1899; Picture books for children